1999
DOI: 10.1073/pnas.96.19.10806
|View full text |Cite
|
Sign up to set email alerts
|

Development of B cells expressing surface immunoglobulin molecules that lack V(D)J-encoded determinants in the avian embryo bursa of Fabricius

Abstract: Immunoglobulin gene rearrangement in avian B cell precursors generates surface Ig receptors of limited diversity. It has been proposed that specificities encoded by these receptors play a critical role in B lineage development by recognizing endogenous ligands within the bursa of Fabricius. To address this issue directly we have introduced a truncated surface IgM, lacking variable region domains, into developing B precursors by retroviral gene transfer in vivo. Cells expressing this truncated receptor lack end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(70 citation statements)
references
References 48 publications
3
67
0
Order By: Relevance
“…After birth, antigen stimulation via bursal epithelium plays a role in the selection of B-cell clones [9]. Using retroviral gene transfer techniques which induce truncated IgM as B-cell receptor, it is clearly demonstrated that the regulation of chicken bursal B-cell development after hatching differs from that in the embryo [107,108]. Therefore further studies are required to determine the effect of external antigens on the selection of B-cells within follicles of both types of PP follicles as well as the functional difference between the ileal and jejunal PP.…”
Section: Ileal and Jejunal Pp As The Site Of B-cell Selection And Thementioning
confidence: 99%
“…After birth, antigen stimulation via bursal epithelium plays a role in the selection of B-cell clones [9]. Using retroviral gene transfer techniques which induce truncated IgM as B-cell receptor, it is clearly demonstrated that the regulation of chicken bursal B-cell development after hatching differs from that in the embryo [107,108]. Therefore further studies are required to determine the effect of external antigens on the selection of B-cells within follicles of both types of PP follicles as well as the functional difference between the ileal and jejunal PP.…”
Section: Ileal and Jejunal Pp As The Site Of B-cell Selection And Thementioning
confidence: 99%
“…Transgenic chickens whose B cells expressed a truncated (V H -less) form of surface IgM underwent rapid cell death in the bursa after hatching, suggesting that signaling through this receptor, presumably by lumenal Ags, is required for proliferation and/or survival of B cells (44).…”
Section: B Cell Stimulation In Galtmentioning
confidence: 99%
“…Line O chicken embryo fibroblasts (CEFs; Regional Poultry Research Laboratories) were transfected with the RCAS-mCD8:chIg vectors as previously described (13). One week after transfection, CEFs were tested for surface expression of the mCD8:chIg chimeric proteins and injected into line 22 chick embryos (Charles River Laboratories) on day 3 of embryogenesis.…”
Section: Retroviral Gene Transfermentioning
confidence: 99%
“…Cell suspensions of bursal cells generated at the time of hatching were also stained for the pan B cell marker ChB6 and as previously described (13).…”
Section: Abs and Flow Cytometrymentioning
confidence: 99%
See 1 more Smart Citation